2x+5/3 > (3x+2)/2 + (3x+1)/6
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a \(2x+2>4\\ \Leftrightarrow2\left(x+1\right)>4\\ \Leftrightarrow x+1>2\\ \Leftrightarrow x>1\)
b \(3x+2>-5\\ \Leftrightarrow3x>-7\\ \Leftrightarrow x>\dfrac{-7}{3}\)
c \(10-2x>2\\ \Leftrightarrow2\left(5-x\right)>2\\ \Leftrightarrow5-x>1\\ \Leftrightarrow-x>-4\\ \Leftrightarrow x< 4\)
d \(1-2x< 3\\ \Leftrightarrow-2x< 2\\ \Leftrightarrow2x>2\\ \Leftrightarrow x>1\)
a)2x+2>4
<=> 2x>4-2
<=>2x>2
<=>x>1
Vậy...
b)3x+2>-5
<=>3x>-5-2
<=>3x>-7
<=>x>\(\dfrac{-7}{3}\)
Vậy...
c)10-2x>2
<=>-2x>-10+2
<=>-2x>-8
<=>x<4
Vậy...
d)1-2x<3
<=>-2x<3-1
<=>-2x<2
<=>x>-1
Vậy...
e)10x+3-5\(\le\)14x+12
<=>10x-2\(\le\)14x+12
<=>10x-14x\(\le\)2+12
<=>-4x\(\le\)14
<=>x\(\ge\)\(\dfrac{-7}{2}\)
Vậy...
f)(3x-1)<2x+4
<=> 3x-2x<1+4
<=>x<5
Vậy...
a: (2x-3)(3x+6)>0
=>(2x-3)(x+2)>0
=>x<-2 hoặc x>3/2
b: (3x+4)(2x-6)<0
=>(3x+4)(x-3)<0
=>-4/3<x<3
c: (3x+5)(2x+4)>4
\(\Leftrightarrow6x^2+12x+10x+20-4>0\)
\(\Leftrightarrow6x^2+22x+16>0\)
=>\(6x^2+6x+16x+16>0\)
=>(x+1)(3x+8)>0
=>x>-1 hoặc x<-8/3
f: (4x-8)(2x+5)<0
=>(x-2)(2x+5)<0
=>-5/2<x<2
h: (3x-7)(x+1)<=0
=>x+1>=0 và 3x-7<=0
=>-1<=x<=7/3
a, \(12-2\left(1-x\right)^2=\left(3x-2\right)\left(2x-3\right)\)
\(< =>12-2\left(1-2x+x^2\right)=6x^2-9x-4x+6\)
\(< =>12-2+4x-2x^2=6x^2-13x+6\)
\(< =>10+4x-2x^2-6x^2+13x-6=0\)
\(< =>-8x^2+17x+4=0< =>\orbr{\begin{cases}x=\frac{17-\sqrt{417}}{16}\\x=\frac{17+\sqrt{417}}{16}\end{cases}}\)
b, \(10x+3-5x=4x+12< =>5x+3-4x-12=0\)
\(< =>x-9=0< =>x=9\)
c, \(11x+42-2x=100-9x-22< =>9x+42-100+9x+22=0\)
\(< =>18x+64-100=0< =>18x-36=0< =>x=\frac{36}{18}=2\)
d, \(2x-\left(3-5x\right)=4\left(x+3\right)< =>2x-3+5x=4x+12\)
\(< =>7x-3-4x-12=0< =>3x-15=0< =>x=\frac{15}{3}=5\)
e, \(2\left(x-3\right)+5x\left(x-1\right)=5x^2< =>2x-6+5x^2-5=5x^2\)
\(< =>2x-11+5x^2-5x^2=0< =>2x-11=0< =>x=\frac{11}{2}\)
f, \(-6\left(1,5-2x\right)=3\left(-15+2x\right)< =>-6\left(\frac{3}{2}-2x\right)=3\left(2x-15\right)\)
\(< =>-9+12x-6x+45=0< =>6x+36=0< =>x=-6\)
g, \(14x-\left(2x+7\right)=3x+12x-13< =>14x-2x-7=15x-13\)
\(< =>12x-7-15x+13=0< =>-3x+6=0< =>x=-2\)
h, \(\left(x-4\right)\left(x+4\right)-2\left(3x-2\right)=\left(x-4\right)^2\)
\(< =>x^2-16-6x+4=x^2-8x+16\)
\(< =>x^2-6x-12-x^2+8x-16=0\)
\(< =>2x-28=0< =>x=\frac{28}{2}=14\)
q, \(4\left(x-2\right)-\left(x-3\right)\left(2x-5\right)=?\)thiếu đề
\(\frac{2x+5}{3}>\frac{3x+2}{2}+\frac{3x+1}{6}\)
\(\Leftrightarrow\)\(\frac{2\left(2x+5\right)}{6}>\frac{3\left(3x+2\right)}{6}+\frac{3x+1}{6}\)
\(\Leftrightarrow\)\(\frac{4x+10}{6}-\frac{9x-6}{6}-\frac{3x+1}{6}>0\)
\(\Leftrightarrow\)\(\frac{4x+10-9x+6-3x+1}{6}>0\)
\(\Leftrightarrow\)\(\frac{-8x+17}{6}>0\)
\(\Rightarrow\)\(-8x+17>0\) (vì \(6>0\))
\(\Leftrightarrow\)\(-8x>-17\)
\(\Leftrightarrow\)\(x< \frac{17}{8}\)
Vậy....